NUCHAL TRANSLUCENCY MARKER FETAL CHROMOSOME CHANGES IN THE FIRST QUARTER - Quispe, José (2015)
Objective: We evaluated the effectiveness of fetal nuchal translucency thickness measurement in routine transvaginal ultrasound screening at 10-14 gestational weeks as a predictor of Downs syndrome in the fetus. Material and methods: A total of 424 pregnant women including one with a twin pregnancy were scanned in the first trimester of pregnancy using a fixed cutoff point of 3 mm for the nuchal translucency measurement. Among these cases 64 had an amniocentesis for fetal karyotyping, other 5 fetuses miscarried spontaneously and one malformed liveborn had also a chromosome analysis. Results: The 410 cases with nuchal translucency thickness less than 3 mm resulted in 409 normal newborns and one baby trisomy 13. A nuchal translucency of 3 mm or greater was detected in 14 pregnancies with the following results: 3 normal babies, 7 with Downs syndrome, 2 with Turners syndrome and 2 were miscarried spontaneously without chromosome analysis. Conclusion: This study demonstrates that first trimester nuchal translucency combined with maternal age is an effective method of screening for fetal chromosomic abnormalities and can be used in routine clinical practice.